Constructing Religious Tolerance Through Digital Dialogue: A Meanings and Media Analysis of the Login Podcast (Episode 6) - Achmad Dzikri Fanshabi; Andi Faisal Bakti; Andi Fakhrullah; Ayu Puja Lestari (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2026)
Religious tolerance in Indonesia remains a significant issue within the context of the country’s religious and cultural diversity, while media representations of tolerance often remain superficial and symbolic. Using Branston and Stafford’s Theory of Meaning and Media, this study interprets how religious tolerance is constructed through digital dialogue in the Login podcast episode “6 Religious Figures Unite on Eid al-Fitr.” This study employs a qualitative case study approach focusing on three units of analysis: the podcast’s verbal and visual elements, 14 selected YouTube comments reflecting variations in audience reception, and in-depth interviews with six religious figures featured in the podcast. The triangulated analysis reveals an imbalance in symbolic representation despite the podcast’s effort to construct a narrative of equality and interfaith harmony. The dominance of denotative meanings over deeper connotative interpretations indicates that media discourse on tolerance tends to emphasize surface-level unity rather than critical engagement with religious differences. These findings highlight the importance of more inclusive and reflective media practices in representing interfaith dialogue and promoting meaningful religious tolerance in digital media.